Islamic Microfinance beyond Credit Access: Women’s Economic Empowerment and Finance Capability Agency Pathway in Indonesia - Emmy Hamidiyah; Ita Sitasari; Mohammadtahir Cheumar; Aselina Endang Trihastuti; Raden Ali Pangestu; Muhamad Fauzi (Darul Yasin Al Sys, 2026)
Although women’s access to microfinance has received considerable scholarly attention, research explaining how access to finance translates into sustained economic empowerment, particularly within women-focused Sharia financial institutions in Indonesia, remains limited. This study aims to develop an integrative framework that explains the mechanisms by which conventional and Islamic microfinance contribute to women’s economic empowerment. A qualitative evidence-synthesis approach was employed through a structured review of peer-reviewed studies published in SINTA 1–2, Scopus-indexed, and Web of Science-indexed journals, with priority given to DOI-verifiable and recent publications while retaining foundational theories of empowerment. Relevant studies were reviewed and synthesised thematically to identify recurring mechanisms, enabling conditions, and constraints. The findings reveal six interdependent mechanisms: access to appropriate finance, business and financial capabilities, social capital, control over income and household decision-making, digital capability, and institutional design. Access to finance can strengthen income, assets, savings, and business continuity; however, its effects on women’s agency remain heterogeneous and may be constrained by repayment pressure, limited control over loan utilisation, weak market access, and restrictive gender norms. The study proposes a Finance–Capability–Agency pathway, demonstrating that Sharia-compliant finance becomes more empowering when integrated with mentoring, savings mechanisms, digital inclusion, and safeguards for women’s decision-making. These findings extend current understanding of financial inclusion and women’s empowerment and provide practical guidance for women-focused Sharia cooperatives in Indonesia and comparable contexts. Further research should empirically test the proposed pathway across different institutional and socio-cultural settings.